2021
DOI: 10.1093/abbs/gmab131
|View full text |Cite
|
Sign up to set email alerts
|

Targeting UPR branches, a potential strategy for enhancing efficacy of cancer chemotherapy

Abstract: Cancer cells are often exposed to cell intrinsic stresses and environmental perturbations that may lead to accumulation of unfolded and/or misfolded proteins in the lumen of endoplasmic reticulum (ER), a cellular condition known as ER stress. In response to ER stress, the cells elicit an adaptive process called unfolded protein response (UPR) to cope with the stress, supporting cellular homeostasis and survival. The ER stress sensors inositol requiring protein 1α (IRE1α), eukaryotic translation initiation fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 109 publications
0
4
0
Order By: Relevance
“…Furthermore, a positive association between ITGAV expression and chemotherapeutic drug sensitivity was exhibted, which has guiding implications in clinical practice. Alvaro et al, have found that in breast cancer, breast epithelial cells detached from ECM can synergistically induce antioxidant response and autophagy through activation of PERK to reduce the level of ROS to delay anoikis [ [37] , [38] , [39] ]. It has also been demonstrated that OGT/O-GlcNAcylation has a high level in many cancers and is closely related to poor survival, unanchored growth, migration, and invasion of lung cancer [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a positive association between ITGAV expression and chemotherapeutic drug sensitivity was exhibted, which has guiding implications in clinical practice. Alvaro et al, have found that in breast cancer, breast epithelial cells detached from ECM can synergistically induce antioxidant response and autophagy through activation of PERK to reduce the level of ROS to delay anoikis [ [37] , [38] , [39] ]. It has also been demonstrated that OGT/O-GlcNAcylation has a high level in many cancers and is closely related to poor survival, unanchored growth, migration, and invasion of lung cancer [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…One problem with the existing anticancer drugs is that a particular drug shows different sensitivities in different individuals. Targeting UPR branches is a promising way to enhance the efficacy of chemotherapy for cancers [ 40 ]. Considering the above problem, we performed a UPR-related IC50 analysis to explore sensitivities and help HNSCC patients obtain personalized medication regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, OA can destroy the homeostasis of the endoplasmic reticulum (ER), but it can be rebuilt by the unfolded protein response (UPR), which is mainly mediated by protein kinase RNA-like ER kinase (PERK), inositol-requiring enzyme 1α (IRE-1α) and activating transcription factor 6 (ATF6) ( Figure 5 ) [ 125 127 ] . Among these pathways, both PERK and IRE-1α can regulate actin cytoskeleton dynamics through the binding with filamin A, and filamin A regulates the action of actin filaments and cytoskeleton dynamics, facilitating cell migration [128] .…”
Section: The Mechanism Of Mgf In Chondrocytes and Cartilage Defectsmentioning
confidence: 99%